Registered Partnerships and LGBT Parenting in the Czech Republic - Zdeněk Sloboda (Gender a Výzkum)
This paper introduces a unique and comprehensive sociological analysis of same-sex partnerships in the Czech Republic, especially in the legally recognised (though limited) form of civil unions (registered partnerships - RP). The analysis combines multiple data sources and methodological approaches, drawing on administrative data from the Ministry of Internal Affairs (n=2710), secondary quantitative data from the Czech Statistical Office and Public Opinion Research Centre/CVVM, and original quantitative (n=882) and qualitative (n=48) data. Focusing on the heteronormative framing of the issue, two main aspects come to the forefront: gender and LGBT parenting. Data show that there has been a small but steadily growing amount of interest in RP, especially among women, in the last six years. However, RP remains very selective and quite 'unpopular'. Although there has been a weakening of the procreative function of marriage, the role of RP in this respect is less clear-cut. On the one hand, it makes some paths to becoming a parent more difficult, while on the other, for some people, it provides a certain symbolic security for their existing family. The article also explores other gender and age characteristics and differences or similarities to marriage.